The Missing (Small) Businesses of Southeast Asia - Schaper, Michael (ISEAS Yusof Ishak Institute, 2020)
EXECUTIVE SUMMARY • There are more than 70 million micro-, small- and medium-sized enterprises (SMEs) in Southeast Asia today that employ over 140 million people and account for 99% of all businesses in the region. • However, there appear to be many “missing businesses,” with significant underreporting and very low figures of SMEs on a per capita basis. As many as 80-90% of SMEs in some countries may be excluded from official counts. • This may be due to the existence of a large informal business sector which is not monitored in many countries; poor data collection methods; or economies being less entrepreneurial SME-focused than elsewhere. • Measuring the true size of the SME sector is difficult because there are no standard definitions across the region, and the quality of published data varies significantly among states. • Governments across the region should consider working through ASEAN to adopt a standardised set of SME definitions and reporting frameworks. This will help identify where the unreported SMEs currently exist.